IMPLEMENTASI BRUTE FORCE ATTACK TERHADAP VIGENERE CIPHER: PENGARUH PANJANG KUNCI DAN PANJANG TEKS - Anzari, Yandi; Rachmawati, Aulia; Damas Fatih, Muhammad; Pariyadi (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2025)
The Vigenere Cipher, although historically significant, remains vulnerable to modern brute force attacks. This study aims to empirically measure how key length and text length independently influence the time required to break the cipher using brute force methods. A pure experimental approach was applied through four test scenarios that combined two key lengths (L=3 and L=5) and two plaintext lengths (22 and 420 characters). The experiments were implemented in Python on a controlled computing environment to ensure result consistency. The findings show that key length has an exponential impact on decryption time, where increasing the key from three to five characters extended the execution time by approximately 370 times. In contrast, text length had a linear effect, with a 19-fold increase in characters leading to only about a 20-fold increase in processing time. In conclusion, the study confirms that cryptographic resistance in the Vigenere Cipher is primarily determined by key length, while text length only increases the computational workload proportionally. Future research is suggested to apply similar brute force analyses to other classical ciphers and explore larger key lengths to model performance limits more comprehensively.